Persebaran, Populasi dan Persentase Serangan Citripestis Sagittiferella Moore (Lepidoptera: Pyralidae) di Sentra Pertanaman Jeruk Provinsi Bali - SANG AYU MADE INTAN PUTRI RAHAYU; KETUT AYU YULIADHI; I WAYAN SUSILA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Distribution, Population and Damage Percentage of Citripestis sagittiferella Moore (Lepidoptera: Pyralidae) at Bali Citrus cultivation Center.This research was conducted at citrus cultivation center in Bali Province in Bangli and Gianyar regencies and in Integrated Pest and Disease Management Laboratory, from August to November 2017. The purpose of this research is to know the distribution, population and damage percentage of citrus fruit borer, Citripestis sagittiferella. This research used survey method. The study area is divided into three zones: zone I (altidute 800-900 m asl), Zone II (altitude >900-1000 m asl), and Zone III (altitude >1000-1.100 m asl). The results showed that C. sagittiferella was found to spread evenly in all zone locations, both zone I, Zone II, and Zone III, with a total population of 6,909 larvae, 4,861 larvae and 3,508 larvae, respectively. The average larval population found in damage citrus fruit is 5.24 larvae per fruit. The percentage of damage on Zone I was 30,57%, Zone II was 28,90%, and Zone III was 27,96%. The correlation test results showed a very strong relationship between the larvae population and the percentage of damage with r = 0.994.